1999
DOI: 10.1074/jbc.274.14.9296
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of I-Branched Poly-N-Acetyllactosamine Synthesis

Abstract: I-branched poly-N-acetyllactosamine is a unique carbohydrate composed of N-acetyllactosamine branches attached to linear poly-N-acetyllactosamine, which is synthesized by I-branching ␤1,6-N-acetylglucosaminyltransferase. I-branched poly-N-acetyllactosamine can carry bivalent functional oligosaccharides such as sialyl Lewis x , which provide much better carbohydrate ligands than monovalent functional oligosaccharides. In the present study, we first demonstrate that I-branching ␤1,6-N-acetylglucosaminyltransfera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 49 publications
2
35
0
Order By: Relevance
“…We have also found that ␤4Gal-TI, iGnT, and I-branching enzyme (IGnT) are involved in the synthesis of I-branched poly-Nacetyllactosamines (30). In the same study, we found that the addition of N-acetyllactosamine repeats to linear N-acetyllactosamine is preferred over the extension of N-acetyllactosamine to an I branch, mainly because galactosylation of a GlcNAc␤136 branch is inefficient (30). Third, we demonstrated that similar size and similar amounts of poly-Nacetyllactosamine are synthesized in both side chains of GlcNAc␤136(GlcNAc␤132)Man␣136Man␤13 R, which was preformed by the action of N-acetylglucosaminyltransferase V. We found that this equal distribution of poly-N-acetyllactosamines is achieved because ␤4Gal-TI and iGnT have complementary branch specificity toward two side chains (31).…”
mentioning
confidence: 78%
See 3 more Smart Citations
“…We have also found that ␤4Gal-TI, iGnT, and I-branching enzyme (IGnT) are involved in the synthesis of I-branched poly-Nacetyllactosamines (30). In the same study, we found that the addition of N-acetyllactosamine repeats to linear N-acetyllactosamine is preferred over the extension of N-acetyllactosamine to an I branch, mainly because galactosylation of a GlcNAc␤136 branch is inefficient (30). Third, we demonstrated that similar size and similar amounts of poly-Nacetyllactosamine are synthesized in both side chains of GlcNAc␤136(GlcNAc␤132)Man␣136Man␤13 R, which was preformed by the action of N-acetylglucosaminyltransferase V. We found that this equal distribution of poly-N-acetyllactosamines is achieved because ␤4Gal-TI and iGnT have complementary branch specificity toward two side chains (31).…”
mentioning
confidence: 78%
“…In I branch formation (30), the GlcNAc␤136 branch in the Gal␤134GlcNAc␤133(GlcNAc␤-136)Gal␤13 R structure is very inefficient for galactosylation, resulting in short I branches as seen in human erythrocytes (57). This inefficiency can be also explained by competition between the Gal terminal in the linear side chain and UDP-Gal for ␤4Gal-TI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, poly-N-acetyllactosamines are preferentially formed in the specific branch in complex type N-glycans, which are formed by ␤1,6-N-acetylglucosaminyltransferase V (102). In addition, core 2 ␤1,6-N-acetylglucosaminyltransferases 1 and 2 and large I ␤1,6-N-acetylglucosaminyltransferases are branching enzymes critical for elongation with poly-N-acetyllactosamines (48,80,81,(103)(104)(105). Discovery of the multiple ␤3Gn-Ts in addition to other multiple glycosyltransferases involved in the biosynthesis of poly-N-acetyllactosamines (e.g.…”
Section: Identification Of Novel ␤13-n-acetylglucosaminyltransferasesmentioning
confidence: 99%